Using meshes for MeSH term enrichment and semantic analyses - Yu, Guangchuang (Bioinformatics, 2018)
Abstract Summary Medical Subject Headings (MeSH) is the NLM controlled vocabulary used to manually index articles for MEDLINE/PubMed. MeSH provides unique and comprehensive annotations for life science. The meshes package implements measurement of the semantic similarity of MeSH terms and gene products to help using MeSH vocabulary in knowledge mining. Enrichment analysis to extract the biological meanings from gene list, expression profile and genomic regions is also provided using MeSH annotation. Meshes supports more than 70 species and provides high quality visualization methods to help interpreting analysis results. Availability and implementation meshes is released under Artistic-2.0 License. The source code and documents are freely available through Bioconductor (https://www.bioconductor.org/packages/meshes). Supplementary information Supplementary data are available at Bioinformatics online.